FAKTOR FAKTOR YANG BERPENGARUH TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - Christina Dwi Astuti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2007)
The aim of this research is to find out which are factors that impact the timelinessof company's financial statement. The object of this research is companies (except banking, securities, insurance, properties and non banking Credit Agencies) listed at Jakarta Stock Exchange for 2001 - 2005 using purposive judgment sampling. From 207 companies, there are 125 companies being samples of this research. Hypothesis test of this research is using logistic regression method, witha= 5% revealed that auditor reputations, audit opinion, size (proxy by market values) and ownership structure (outsider and insider) have impact to the timeliness of financial statement, but leverage (proxy by debt to equity ratio), ages and profitability (proxy by ROA) haven't impact to the timeliness of financial statement.